1994
DOI: 10.1007/bf00150353
|View full text |Cite
|
Sign up to set email alerts
|

Influence of mulching on the pattern of growth and water use by spring wheat and moisture storage on a fine textured soil

Abstract: Eight tonnes ha -1 of stubble were used to mulch spring wheat (Triticum aestivum) on a fine textured soil with the aim of controlling both transpiration and soil evaporation during the wet pre-anthesis phase to increase moisture supply during grain filling in the eastern wheatbelt of Western Australia. Mulching reduced leaf area per plant by reducing the culm number; consequently the green area index was reduced. Reduced culm number was associated with low soil temperature which at 50 mm depth averaged 7°C low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 18 publications
2
10
0
Order By: Relevance
“…Plant stand reduction was most likely caused by physical smothering. Yunusa et al (1994) found no difference in the plant population density between control plots and wheat plots mulched with wheat straw at a rate of 8 t ha -1 when mulch was applied 36 d after seeding (at floral initiation). Nevertheless, the loss of plants at Carman 2003 suggests that a rate of 6.6 t ha -1 of alfalfa mulch applied at the three-leaf stage may be excessive for optimum wheat plant establishment.…”
Section: Stand Establishment and Surface Soil Water Contentmentioning
confidence: 78%
See 1 more Smart Citation
“…Plant stand reduction was most likely caused by physical smothering. Yunusa et al (1994) found no difference in the plant population density between control plots and wheat plots mulched with wheat straw at a rate of 8 t ha -1 when mulch was applied 36 d after seeding (at floral initiation). Nevertheless, the loss of plants at Carman 2003 suggests that a rate of 6.6 t ha -1 of alfalfa mulch applied at the three-leaf stage may be excessive for optimum wheat plant establishment.…”
Section: Stand Establishment and Surface Soil Water Contentmentioning
confidence: 78%
“…Schäfer et al (2002) investigated a system where strips of perennial forage crops were grown between strips of annual crops, and a modified forage harvester was used to apply the forage mulch to bare soil, or on top of growing crops. With such a system, the mulch provides nutrients to a crop as it decomposes (Fribourg and Bartholomew 1956), while potentially suppressing weeds (Teasdale et al 1991) and conserving soil moisture (Yunusa et al 1994).…”
mentioning
confidence: 99%
“…Johns (1982) investigated soil evaporation under three evaporative regimes (Ep <3mm, 3-6 mm and >6 mm day −1 ) and showed that stage one and stage two evaporation could be clearly elucidated at Ep's of >3 mm and 3-6 mm day −1 but reported stage one evaporation at Ep > 6 mm day −1 to be virtually non-existent. Similarly, in a study contrasting the evaporative models of Ritchie (1972) and Boester and Stroosnijder (1986), Yunusa et al (1994) showed that stage one evaporation was more apparent under low than high evaporative conditions.…”
Section: Effect Of Row Spacing On Soil Evaporationmentioning
confidence: 91%
“…As a result, alternative methods for estimating Es using either empirical (Cooper et al, 1983), semi analytical (Ritchie, 1972) or modelling approaches (Lascano, 1987) have been adopted. However, while these approaches are convenient, only a few studies exist (ie, Allen, 1990;Yunusa et al, 1993a;Yunusa et al, 1994;Eastham and Gregory, 2000) where alternate methods to estimate Es have been compared to microlysimetry.…”
Section: Introductionmentioning
confidence: 98%
“…The high effect during the energy limited first stage of evaporation decreases during the flux limited second stage and diffusion limited third stages of evaporation (Steiner 1994). Long-term moisture conservation during prolonged dry periods is less feasible (Yunusa et al 1994).…”
Section: Mulchingmentioning
confidence: 99%